2016
DOI: 10.1093/nar/gkw621
|View full text |Cite
|
Sign up to set email alerts
|

Set7 mediated interactions regulate transcriptional networks in embryonic stem cells

Abstract: Histone methylation by lysine methyltransferase enzymes regulate the expression of genes implicated in lineage specificity and cellular differentiation. While it is known that Set7 catalyzes mono-methylation of histone and non-histone proteins, the functional importance of this enzyme in stem cell differentiation remains poorly understood. We show Set7 expression is increased during mouse embryonic stem cell (mESC) differentiation and is regulated by the pluripotency factors, Oct4 and Sox2. Transcriptional net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 53 publications
(79 reference statements)
3
30
0
Order By: Relevance
“…Additional evidence further supports SETD7 involvement in hESCs differentiation, as SETD7 knockdown impedes silencing of pluripotent markers and delays differentiation 49 . These findings support that SETD7 is upregulated during cell differentiation 45,47,49,50 . Accordingly, increased Setd7 levels during mESC differentiation mediate Setd7-dependent H3K4me1 to regulate genes associated with differentiation and induce smooth muscle-associated genes 47 .…”
Section: Ezh2supporting
confidence: 80%
See 1 more Smart Citation
“…Additional evidence further supports SETD7 involvement in hESCs differentiation, as SETD7 knockdown impedes silencing of pluripotent markers and delays differentiation 49 . These findings support that SETD7 is upregulated during cell differentiation 45,47,49,50 . Accordingly, increased Setd7 levels during mESC differentiation mediate Setd7-dependent H3K4me1 to regulate genes associated with differentiation and induce smooth muscle-associated genes 47 .…”
Section: Ezh2supporting
confidence: 80%
“…More recently, a flurry of studies has reported substantial roles for SETD7 involvement in ESC pluripotency both through transcriptionally regulated pathways, and direct methylation of pluripotent substrates, such as SOX2 and LIN28A 45,46 . Oct4 and Sox2 suppress Setd7 expression levels in mESCs by binding to its promoter region, whereas upon differentiation, removal of these pluripotency factors induces Setd7 transcription by activating H3K4me3 marks at bivalent domains 47 . Consistent with these findings, Babaie et al reported upregulation of SETD7 in hESCs after knockdown of OCT4, supporting intricate roles of these factors as it pertains to ESC pluripotency 48 .…”
Section: Ezh2mentioning
confidence: 99%
“…The stimulation of transcriptional activation involves numerous diverse classes of proteins known as transcription coactivators 30,31 . SET7/9 catalyzes the monomethylation of histone H3 lysine 4 (H3K4me1) and nonhistone proteins such as serum response factor in embryonic stem cells to regulate gene expression as coactivators 32 . In breast cancer, as reported by Subramanian K. et al 33 , estrogen receptor α (ER) is a liganddependent transcription factor that can be directly methylated by SET7/9.…”
Section: Discussionmentioning
confidence: 99%
“…A novel in vivo assay combining in situ hybridization and a proximity ligation assay provides further evidence that the H3K4me2 mark at the Myh11 locus is restricted to differentiated SMCs in vivo [68]. Similarly, a histone H3 lysine 4 mono-methylation (H3K4me1) catalysed by the Set7 lysine methyltransferase is considered a further hallmark of transcriptionally active chromatin [69]. Recent transcriptional network analyses has revealed that SMC differentiation genes are also subject to Set7-mediated regulation [69].…”
Section: Epigenetic Control Of Smc Differentiation Genesmentioning
confidence: 99%
“…Similarly, a histone H3 lysine 4 mono-methylation (H3K4me1) catalysed by the Set7 lysine methyltransferase is considered a further hallmark of transcriptionally active chromatin [69]. Recent transcriptional network analyses has revealed that SMC differentiation genes are also subject to Set7-mediated regulation [69]. Hence, several cell-specific epigenetic mechanisms govern the expression of cellular markers during SMC differentiation.…”
Section: Epigenetic Control Of Smc Differentiation Genesmentioning
confidence: 99%